Effect of integrated crop management on seed quality in mungbean (Vigna radiata) - JITENDER, JITENDER; PUNIA, R C; SANGWAN, V P S; JAKHAR, SATBIR; HEMENDER, HEMENDER (The Indian Journal of Agricultural Sciences, 2018)
The present study was conducted at CCSHAU, Hisar during 2015-16 on mungbean var. MH 421 with sixteen treatment combination to assess the effect of integrated crop management on seed quality. The results revealed that treatment, recommended dose of fertilizer (RDF) + recommended weed management (RWM) + recommended pest management (RPM) showed significantly higher test weight (46.38), (45.52), germination percentage (93.67), (91.00), seedling length (48.33), (46.00), seedling dry weight (26.20, 20.23), vigour index-I (4527, 4186), vigour index-II (2454, 1841), germination after accelerated ageing test (76.00, 71.33), in summer and kharif season, respectively, over control.